Between Milieu and Vacuum – Organizational, Programmatic, and Electoral Strategies of the Former Party of Democratic Socialism (PDS) and the Communist Party of Bohemia and Moravia (KSČM) Reexamined - Seongcheol Kim (Politologický časopis - Czech Journal of Political Science, 2017)
This paper proposes an updated approach to explaining two outcomes unforeseen by the existing comparative literature on post-communist successor parties: 1) the electoral stabilization (and even growth) and 2) the divergent developments of the Party of Democratic Socialism (PDS; later DIE LINKE) in Germany and the Communist Party of Bohemia and Moravia (KSČM). The paper proceeds by integrating a critical reexamination of earlier studies' organizational and programmatic explanations of electoral success with an analysis of the party-system level of government-opposition signaling and positioning vis-à-vis other parties, which can be expected to take on heightened importance in `third-generation elections.' It is argued that both parties' successes were tied to a strategic orientation toward going beyond their confinement in a delimited electoral `milieu' and occupying a wider electoral `vacuum' to the left of their Social Democratic competitors, albeit with early programmatic modernization and delayed organizational centralization in the PDS as opposed to a near-total continuity of programmatic non-reform and decentralized organization in the KSČM. The findings suggest that earlier studies specifically overlook the impact of subsequent (`third-generation') iterations of party competition on successor-party success as well as the mediation of organizational and programmatic factors by the party-system level.
Keywords: 300; Czech Republic; electoral politics; Germany; party system; post-communist successor parties